1999
DOI: 10.1093/sleep/22.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Role of GABAA Receptors in the Regulation of Sleep: Initial Sleep Responses to Peripherally Administered Modulators and Agonists

Abstract: This paper reviews the sleep effects of systemically administered agonistic modulators of GABAA receptors, including barbiturates, benzodiazepines, zolpidem, zopiclone and neuroactive steroids, and the selective GABAA agonists muscimol and THIP. To assess the involvement of GABAA receptors in the physiologic regulation of sleep, the article emphasizes the hypnotic properties shared by agonistic modulators and by the selective agonists of the GABAA receptor complex. In both rats and normal sleeping individuals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
118
3
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(134 citation statements)
references
References 0 publications
7
118
3
6
Order By: Relevance
“…In rats, benzodiazepines reduce sleep latency, promote non-REMS (in particular its substate pre-REMS) and transiently suppress REMS (reviewed in Lancel 1999). Furthermore, such compounds depress slow frequency components and augment spindling in the EEG within non-REMS, while enhancing high-frequency activity in all vigilance states (Hashimoto et al 1992;Lancel et al 1996;Mandema et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, benzodiazepines reduce sleep latency, promote non-REMS (in particular its substate pre-REMS) and transiently suppress REMS (reviewed in Lancel 1999). Furthermore, such compounds depress slow frequency components and augment spindling in the EEG within non-REMS, while enhancing high-frequency activity in all vigilance states (Hashimoto et al 1992;Lancel et al 1996;Mandema et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In rats, benzodiazepines are established to shorten the latency to non-REMS, promote particularly pre-REMS, depress slow frequency components and enhance spindling in the electroencephalogram (EEG) within non-REMS (reviewed in Lancel 1999). One notable difference is that benzodiazepines transiently suppress REMS, an effect till now not observed for neurosteroids.…”
mentioning
confidence: 99%
“…They induce dose-dependent increases of non-rapid eye movement (NREM) sleep, a reduction of REM sleep in humans and a typical BZ ''fingerprint,'' consisting of a reduction in delta activity in humans and rats, an increase of sigma activity in humans, and high-frequency activity in rats (8-15). These effects are common for agonists acting at the BZ site, irrespective of whether they are BZ or non-BZ compounds such as zolpidem and zopiclone (15)(16)(17).To assess whether the ␣1 GABA A receptors mediate not only the sedative action of Dz but also its effects on sleep, the sleep EEG and motor activity were compared in ␣1(H101R) and wild-type mice. Surprisingly, we found that the BZ fingerprint in the sleep EEG was present in both genotypes, indicating that these changes in the sleep EEG are mediated by GABA A receptors other than ␣1, in contrast to the sedative action, which is mediated by ␣1 receptors (5, 6).…”
mentioning
confidence: 99%
“…They induce dose-dependent increases of non-rapid eye movement (NREM) sleep, a reduction of REM sleep in humans and a typical BZ ''fingerprint,'' consisting of a reduction in delta activity in humans and rats, an increase of sigma activity in humans, and high-frequency activity in rats (8)(9)(10)(11)(12)(13)(14)(15). These effects are common for agonists acting at the BZ site, irrespective of whether they are BZ or non-BZ compounds such as zolpidem and zopiclone (15)(16)(17).…”
mentioning
confidence: 99%
“…Diferentemente dos hipnóticos não benzodiazepínicos, os quais são agonistas moduladores do GABA, pois agem em sítios alostéricos, induzindo mudanças na conformação do receptor GABA-A; o gaboxadol é propriamente um agonista, pois assim como o GABA, ele ativa diretamente os receptores GABA-A, constituindo-se assim numa nova classe de hipnóticos 36 . Resultados iniciais de estudos em idosos mostraram melhora da qualidade subjetiva do sono; entretanto, pode estar sujeito às mesmas restrições que a tiagabina em termos de segurança para pacientes com distúrbios do sono.…”
Section: Outras Moléculas Em Desenvolvimento 1) Tasimelteonunclassified